Assessment of stakeholders participation in forest road maintenance in a Nigerian forest estate. (2011)
A study was conducted to assess the stakeholders' participation in forest roads maintenance at the Ondo State Afforestation Project (OSAP) in Odigbo Local Government Area of Ondo State. Forest roads maintenance is a tool for sustainable forest management. Using simple random sampling method, respondents were selected from the study population which included staff of the Ondo State Afforestation Project, and residents of the communities within the enclaves in the area such as llulitun, Ilege, Lisagbede, Makinde, Ogunlepa I, Ogunlepa II. Results showed that 84.30% of the stakeholders expressed concern about the present condition of the road, 4.30% were not interested on importance attached to road maintenance while 11.40% of the respondents were indifferent. Data obtained from the professional staff of OSAP show that only 20% of the stakeholders actually participated in forest roads maintenance. Although 34.35% of other stakeholders within the forse estate (farmers and timber contractors) claimed to be involved in grading of roads but majority (65.70%) of the stakeholders said they did not participate in road maintenance. The implication of the findings indicate that roads leading to forest areas have not been given adequate attention through stakeholders participation. This has resulted in road degradation thereby causing hardship to smooth transportation of resources and human beings. It is recommended that all stakeholders' be encouraged to participate actively in road maintenance in the study area in other to promote sustainable management of forest resources.